Social soil science as a new approach in soil science - Позняк, Степан Павлович; Позняк, С. П.; Pozniak, Stepan P.; Гавриш, Наталія Степанівна; Гавриш, Н.С.; Гавриш, Наталия Степановна; Havrysh, Natalia S. (ResearchGate Corporation, 2020)
The article contains the authors’ reflections on the formation and substantiation of many aspects in soil science, concerning its connections with social sciences. Arguments about the exceptional importance of soil resources in the modern world and the importance of scientific research in soil science, which can become an important instrument of solving social problems, are found. It is shown that soil resources, being the basis of agricultural development, are the long-term capital through which different nations exist and develop. In order to maintain the normal living conditions of the population and to improve them, it is important to use this global resource wisely. The attitude of people to the soil is recognized as fundamental for nation’s sustainable development and, moreover, the life expectancy of a civilization may depend on the people attitude to soils. In order to maintain collective well-being of people, a long-term interest of the society in soil protection needs to be reoriented – this should become a priority task for our civilization. The current state of soils can be a characteristic of the development of society as well as a criterion for assessing the activity of government and social stability in the country.

Стаття містить роздуми авторів про формування та обгрунтування багатьох аспектів ґрунтознавства та його зв’язків із суспільними науками. Знайдено аргументи про виняткове значення ґрунтових ресурсів у сучасному світі та важливість наукових досліджень у галузі ґрунтознавства, які можуть стати важливим інструментом вирішення соціальних проблем. Показано, що ґрунтові ресурси, будучи основою розвитку сільського господарства, є довгостроковим капіталом, завдяки якому існують і розвиваються різні нації. Щоб підтримувати нормальні умови життя населення та покращувати їх, важливо розумно використовувати цей глобальний ресурс. Ставлення людей до ґрунту визнано основою сталого розвитку нації, і, крім того, тривалість життя цивілізації може залежати від ставлення людей до ґрунтів. Для підтримки колективного добробуту людей довгостроковий інтерес суспільства до охорони ґрунтів потрібно переорієнтувати - це має стати пріоритетним завданням нашої цивілізації. Сучасний стан ґрунтів може бути характеристикою розвитку суспільства, а також критерієм оцінки діяльності влади та соціальної стабільності в країні.

Статья содержит размышления авторов о формировании и обоснование многих аспектов почвоведения и его связей с общественными науками. Приведены аргументы об исключительном значении почвенных ресурсов в современном мире и важность научных исследований в области почвоведения, которые могут стать важным инструментом решения социальных проблем. Показано, что почвенные ресурсы, являясь основой развития сельского хозяйства, являются долгосрочным капиталом, благодаря которому существуют и развиваются различные нации. Чтобы поддерживать нормальные условия жизни населения и улучшать их, важно разумно использовать этот глобальный ресурс. Отношение людей к почве признано основой для устойчивого развития нации, и, кроме того, продолжительность жизни цивилизации может зависеть от отношения людей к почвам. Для поддержания коллективного благосостояния людей долгосрочный интерес общества к охране почв нужно переориентировать - это должно стать приоритетной задачей нашей цивилизации. Современное состояние почв может быть характеристикой развития общества, а также критерием оценки деятельности власти и социальной стабильности в стране.
Pozniak S. Social soil science as a new approach in soil science / S. Pozniak, N. Havrysh // Polish Journal of Soil Science. – V. 53 (1). – ResearchGate Corporation, 2020. – Р. 73-79.
Keywords: social soil science; soil resources; soil protection; fertility of soils; soil conservation technologies; соціальне ґрунтознавство; ґрунтові ресурси; захист ґрунтів; родючість ґрунтів; технології збереження ґрунтів; социальное почвоведение; почвенные ресурсы; защита почв; плодородие почв; почвозащитные технологии; Research Subject Categories::FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING::Soil science; Research Subject Categories::LAW/JURISPRUDENCE